PEMBENTUKAN PENGETAHUAN LINGKARAN MELALUI PEMBELAJARAN ASIMILASI DAN AKOMODASI TEORI KONSTRUKTIVISME PIAGET - author Tri Yuni Hendrowati (Universitas Muhammadiyah Pringsewu, 2015)
Teachers are still considered the only centers of learning in mathematics, in the sense that only teachers in the delivery of materials that play an active role in the classroom, so that the learning process becomes ineffective. It can be to affect the low students' result. Efforts are being made to overcome this is to involve students actively and creatively in the process of formation of knowledge. The Piaget's theory of constructivism assimilation and accommodation is a learning that allows students to be active and critical in the process of learning and allow students to construct their own knowledge based on experience and knowledge they have. The population was all of the students in eight grade of SMP 25 Bandar Lampung in the academic year of 2013-2014. The samples of the research were taken by using the cluster random sampling technique. To obtain data through the students' result in the form of an essay test consists of 5 items, then the data were analyzed using t-test. Based on hypothesis test, it can be included that, there is influence the Piaget's theory of constructivism assimilation and accommodation to the improvement of knowledge formation about circle. Keywords: The Learning Assimilation and Accomodation, The Piaget's Theory of Constructivism, The Knowledge Formation About Circle